Zastosowanie drzew klasyfikacyjnych w analizie klas ukrytych - Kasprzyk, Iwona (An Application of the Classification Tree in the Latent Class Analysis, 2008)
The latent class analysis is one of multivariate analysis techniques of the contingency table which is based on discrete data. This method was introduction by Lazarsfeld [1968]. The classification and regression tree is a nonparametric technique which was proposed by Breiman et al. [1984], The main aim of this article is to show how we can use the classification tree to reduce the number of variables which can be put into the latent class analysis. Additionally the article shows the barycentric coordinates graph which permits to describe the relations among categories of variables.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 276-285